1988
DOI: 10.1073/pnas.85.19.7307
|View full text |Cite
|
Sign up to set email alerts
|

Human genes for complement components C1r and C1s in a close tail-to-tail arrangement.

Abstract: Complementary DNA clones for human Cls were isolated from cDNA libraries that were prepared with poly(A)+ RNAs of human liver and HepG2 cells. A clone with the largest cDNA insert of 2664 base pairs (bp) was analyzed for its complete nucleotide sequence. It contained 202 bp of a 5' untranslated region, 45 bp of coding for a signal peptide (15 amino acid residues), 2019 bp for complement component Cls zymogen (673 amino acid residues), 378 bp for a 3' untranslated region, a stop codon, and 17 bp of a poly(A) ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

1991
1991
2002
2002

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…In fact, activated C1s is immunostained arround vessels invading into cartilage (H. Sakiyama, unpublished work). Since C1s has widespread distribution in many tissues (Kusumoto et al 1988;Sakiyama et al 1991), it may have a specific function in each tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, activated C1s is immunostained arround vessels invading into cartilage (H. Sakiyama, unpublished work). Since C1s has widespread distribution in many tissues (Kusumoto et al 1988;Sakiyama et al 1991), it may have a specific function in each tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Combined and partial C1s and C1r deficiency has also been reported in several patients including four siblings, two of whom developed discoid lupus and rheumatoid arthritis (18), and a 60-year-old woman with SLE (19). The genetic defect of combined C1r/C1s deficiency has not yet been elucidated but might be related to the close location of the two genes on chromosome 12 (12p13) (7). A few cases of selective C1r deficiency have also been reported, associated with lupus-like syndrome (20,21) or susceptibility to infection (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The major synthesis site of serum C1s is the liver. However, C1s gene expression has been found in most other tissues, including brain, kidney, stomach, and muscle (Kusumoto et al 1988;Sakiyama et al 1991), and in several types of cultured cells, such as monocytes (Bensa et al 1983), endothelial cells (Morris et al 1978), and fibroblasts (Kats and Strunk 1989). By immunostaining (Sakiyama et al 1991 and in situ hybridization (Toyoguchi et al 1996), we have shown that C1s is also synthesized by chondrocytes and that the synthesis increases in accordance with chondrocyte hypertrophy.…”
Section: Introductionmentioning
confidence: 96%